About the article entitled “Nonalcoholic fatty liver disease in patients with type 2 diabetes: a review article” - Arias Chipana, Kenny Brando (2024)
Dear Madam Editor: I have read with great interest the article entitled “Nonalcoholic fatty liver disease in patients with type 2 diabetes: a review article” (1) by Gonzalo Miranda, published in volume 23, issue 2 of Horizonte Médico (Lima) journal, which concludes that the high prevalence of type 2 diabetes mellitus (T2DM) and nonalcoholic fatty liver disease (NAFLD) could lead to an alarming public health problem in the future because of the consequences in terms of mortality and morbidity associated with these diseases. For this reason, it is deemed appropriate to reflect on the subject, taking into account its great importance.